Curdlan sulfate–O-linked quaternized chitosan nanoparticles: potential adjuvants to improve the immunogenicity of exogenous antigens via intranasal vaccination - Zhang S (Dove Medical Press, 2018)
Shu Zhang,1 Shengshi Huang,2 Lu Lu,1 Xinlei Song,1 Pingli Li,3 Fengshan Wang1,2 1Key Laboratory of Chemical Biology of Natural Products (Ministry of Education), Institute of Biochemical and Biotechnological Drugs, School of Pharmaceutical Sciences, Shandong University, Jinan, Shandong, 2National Glycoengineering Research Center, Shandong Provincial Key Laboratory of Carbohydrate Chemistry and Glycobiology, Shandong University, Jinan, Shandong, 3Institute of Clinical Pharmacology, Qilu Hospital of Shandong University, Jinan, Shandong, China Introduction: The development of ideal vaccine adjuvants for intranasal vaccination can provide convenience for many vaccinations. As an ideal intranasal vaccine adjuvant, it should have the properties of assisting soluble antigens to pass the mucosal barrier and potentiating both systemic and mucosal immunity via nasal administration. Methods: By using the advantages of polysaccharides, which can promote both T-helper 1 and 2 responses, curdlan sulfate (CS)–O-(2-hydroxyl)propyl-3-trimethyl ammonium chitosan chloride (O-HTCC) nanoparticles were prepared by interacting CS with O-HTCC, and the adjuvancy of the nanoparticles was investigated. Results: The results showed that the polysaccharide-based nanoparticles induced the proliferation and activation of antigen-presenting cells. High protein-loading efficiency was obtained by testing with the model antigen ovalbumin (Ova), and the Ova adsorbed onto the cationic CS/O-HTCC complexes was taken up easily by the epithelium. To evaluate the capacity of the Ova/CS/O-HTCC nanoparticles for immune enhancement in vivo, we collected and analyzed immunocytes, serum, and mucosal lavage fluid from intranasally vaccinated mice. The results showed that Ova/CS/O-HTCC nanoparticles induced activation and maturation of antigen-presenting cells and provoked the proliferation and differentiation of lymphocytes more significantly compared to the immunization of Ova mixed with aluminum hydroxide gel. Furthermore, CS/O-HTCC evoked a significantly higher level of Ova-specific antibodies. Conclusion: Therefore, these results suggest that CS/O-HTCC nanoparticles are ideal vaccine adjuvants for soluble antigens used in intranasal or mucosal vaccination. Keywords: curdlan sulfate, O-linked quaternized chitosan, nasal mucosa immunization, nanoparticle, adjuvant, ovalbumin, immune response